Drug-Induced Idiosyncratic Agranulocytosis - Infrequent but Dangerous - Rattay, Bernd; Benndorf, Ralf A. (Frontiers in Pharmacology, 2021)
Drug-induced agranulocytosis is a life-threatening side effect that usually manifests as a severe form of neutropenia associated with fever or signs of sepsis. It can occur as a problem in the context of therapy with a wide variety of drug classes. Numerous drugs are capable of triggering the rare idiosyncratic form of agranulocytosis, which, unlike agranulocytosis induced by cytotoxic drugs in cancer chemotherapy, is characterised by "bizzare" type B or hypersensitivity reaction, poor predictability and a mainly low incidence. The idiosyncratic reactions are thought to be initiated by chemically reactive drugs or reactive metabolites that react with proteins and may subsequently elicit an immune response, particularly directed against neutrophils and their precursors. Cells or organs that exhibit specific metabolic and biotransformation activity are therefore frequently affected. In this review, we provide an update on the understanding of drug-induced idiosyncratic agranulocytosis. Using important triggering drugs as examples, we will summarise and discuss the chemical, the biotransformation-related, the mechanistic and the therapeutic basis of this clinically relevant and undesirable side effect.